The effect of light curing intensity on bulk-fill composite resins: heat generation and chemomechanical properties - Wendy Jingwen Wang; Anastasiia Grymak; John Neil Waddell; Joanne Jung Eun Choi (Medical Journals Sweden, 2021)
Objectives The aim of this study was to assess the effect of light curing intensity and wavelength spectrum on heat generation and chemomechanical properties of bulk-fill composites. Methods Four bulk-fill restorative materials (Filtek bulk-fill, Tetric PowerFill bulk-fill, Beautifil Bulk restorative and Admira Fusion X-tra were used in this study. A total of 100 cylindrical specimens of each composite (n = 25/group) were prepared, then cured using monowave light curing unit (LCU) with a single light intensity of 1470 mW/cm2, and polywave LCU with three different light intensities (1200,2100, 3050mW/cm2). The temperature change during polymerisation was measured by five K-type thermocouples placed in each 1 mm layer from top to bottom. Hardness and degree of conversion of composites at each level were evaluated. Results were statistically analysed. Results The use of polywave LCU resulted in statistically higher peak temperatures ranging between 31.4-63.5 °C compared to the temperature generated by monowave LCU ranging between 29.5-60 °C (p < .05). Curing using polywave LCU with the highest light intensity of 3050 mW/cm2 caused the highest peak temperature irrespective of the composite types. There was no significant difference in hardness with different light curing intensities and curing times, regardless of the bulk-fill resin materials (p > .05). A positive correlation was also found between the hardness and the DoC of the four bulk-fill composites. Conclusion The change in temperature during polymerisation of bulk-fill composites were found to be proportional to the increase in light curing intensity. Mechanical properties of the bulk-fill composites were dependent on the composition and the type of photoinitiators.